The co-operative input the development of the pilot hillside agricultural project (PHILAGRIP) South Trelawny - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas, 2021)
82 páginas pdf.